IMPLIKATUR WACANA HUMOR GELAR WICARA INI TALKSHOW DI NET TV - Irfansyah, Nur; Sumarlam, Sumarlam (BAHASTRA, 2017)
The goal reached in this study is to describe and explain (1) implicature entity; (2) violation of cooperative principle; and (3) violation of politeness principle. The research is qualitative approach in content analysis and pragmatics theory designed. Data is humor discourse on Ini Talkshow program at NET TV, collected by recoding and taking a note. Data validation investigated by applying data triangulation. Then, data analyzed by using interactive models. The result study presented that (1) humor discourse of impicature entity on Ini Talkshow such as mentioning, expressing, refusing, instituating, judging, accusing, claiming, asking/want, mocking, evicting, and threatening; (2) violated of cooperative principle maxim such as quantity, quality, relevance, and manner; and (3) besides violating cooperative principle, the implicature expressing also violated positive and negative politeness. This violation was done deliberately in case to create the humor sense of audience minds.